FDI and growth: the role of institutional quality - Tun, Yin Li; Wan Ngah, Wan Azman Saini; Law, Siong Hook (2014)
This study is aim to investigate the importance of institutions for the growth-enhancing effect of FDI in a panel of 78 countries over 1981-2005 periods. Interaction term between FDI and institutional quality is imposed in the estimation to capture this mediation effect. While using system GMM method, the findings highlight the complementary between FDI and institutional quality where the impact of FDI on growth actually depends on the quality of institution in the host countries.